2018
DOI: 10.1186/s12974-018-1111-y
|View full text |Cite
|
Sign up to set email alerts
|

Early alpha-lipoic acid therapy protects from degeneration of the inner retinal layers and vision loss in an experimental autoimmune encephalomyelitis-optic neuritis model

Abstract: BackgroundIn multiple sclerosis (MS), neurodegeneration is the main reason for chronic disability. Alpha-lipoic acid (LA) is a naturally occurring antioxidant which has recently been demonstrated to reduce the rate of brain atrophy in progressive MS. However, it remains uncertain if it is also beneficial in the early, more inflammatory-driven phases. As clinical studies are costly and time consuming, optic neuritis (ON) is often used for investigating neuroprotective or regenerative therapeutics. We aimed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 57 publications
0
38
0
Order By: Relevance
“…45 In animal model studies, use of a putative neuroprotective agent, α-lipoic acid, reduced the loss of INL thickness over time. 54 Unfortunately, this apparent protection was not associated with better visual outcomes.…”
Section: Inner Nuclear Layermentioning
confidence: 99%
“…45 In animal model studies, use of a putative neuroprotective agent, α-lipoic acid, reduced the loss of INL thickness over time. 54 Unfortunately, this apparent protection was not associated with better visual outcomes.…”
Section: Inner Nuclear Layermentioning
confidence: 99%
“…OKR monitoring provides a functional readout of the neurodegeneration seen by OCT. In these experiments, visual function assessed as spatial frequency by OKR, and neuroaxonal damage assessed as IRL thinning by OCT, were in close correlation 17 . Various protocols can be employed to examine the visual acuity by changing the spatial or temporal frequency, contrast sensitivity, orientation or speed of the moving grid.…”
mentioning
confidence: 59%
“…The examination of the visual pathway, as a part of the central nervous system, has been proven to be an effective starting point in addressing not only ophthalmologic 1,2,3,4,5 , but also neurologic 6,7,8,9,10,11,12,13,14,15,16 questions. In recent years, OCT and OKR have been identified as useful analytic, non-invasive tools to evaluate a large variety of retinopathies and retinal manifestations in various rodent models 17,18,19,20,21,22,23,24,25 . OCT allows for fast and high resolution in vivo visualization of the retinal morphology and structure in mice and rats, with results in good accordance with histological sections of the animals retinae 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The neuroprotective capacity of LA in the neurodegeneration has been reported recently, which demonstrated that therapeutic treatment with LA preserved the survival of the retinal ganglion cells 71 . Moreover, Melli et al 72 showed that LA exerts neuroprotective effects by preventing the mitochondrial dysfunction via the expression of the mitochondrial iron chaperone or iron storage protein, frataxin.…”
Section: Confocal Imaging Of Microtubule Cytoskeleton In Sh-sy5y Livimentioning
confidence: 90%